Metode Saintifik Dipadukan dengan Konsep Ajaran Tri Pramana untuk Meningkatkan Aktivitas dan Prestasi Pendidikan Agama Hindu - Junilyani, Dayu Putu; Sucita, Dewa Nyoman; Seriasih, Ni Wayan (Jurnal Widya Sastra Pendidikan Agama Hindu, 2023)
The purpose of this study was to improve the activity and learning achievement of XII Multimedia students of SMK TI Bali Global Singaraja in the 2022/2023 academic year by applying the scientific method combined with the concept of Tri Pramana teachings. The subjects in this study were all XII Multimedia students of SMK TI Bali Global Singaraja who are Hindu. In this study, researchers set targets for class average (M) 80, Absorption (DS) 80%, Classical Learning Completeness 80% and student learning activity 80%. Judging from the results of this study, that the application of scientific methods combined with the concept of Tri Pramana teachings can increase the activity and learning achievement of XII Multimedia students of SMK TI Bali Global Singaraja in Hinduism and Budi Pekerti subjects. This is shown from the increase in student learning activity results in cycle I 56% to 83% in cycle II. Increased student learning achievement from cycle I with a class average of 77,03 to 82.22 in cycle II. The increase in absorption was 77,02% in cycle I to 82.22% in cycle II. And an increase in classical learning completeness of 62,96% in cycle I to 85.19% of KKM 80. The conclusion is that the scientific method is combined with the concept of Tri Pramana teachings as an effort to improve the quality and quality of student education, especially in the field of Hindu Religious Education and Budi Pekerti.